Immigrant self-employment in turbulent times: A decade with refugee crisis and the COVID-19 pandemic - Mats Hammarstedt; Per Skedinger (Research Institute of Industrial Economics (IFN), 2024)
We examine immigrant self-employment in Sweden during 2011-2021 - a turbulent decade with a large influx of refugees into the country and the outbreak of the global COVID-19 pandemic. Four outcome variables are investigated: the probability of self-employment, the probability of entry into and exit from this state and earnings of the self-employed. This is done for different cohorts of immigrants from Africa and Asia and for different types of businesses, unincorporated and incorporated firms. We find that immigrants have lower business earnings and higher exit rates from self-employment than natives, which is in line with previous research. It also turns out that the period in which the immigrants arrived to Sweden and the type of business they are engaged in have important implications for outcomes. In most cases, outcomes are more favorable for the earliest of the three cohorts we study, those who came to Sweden up to the turn of the millennium, and less so for the latest arrivals during the turbulent decade. Moreover, immigrants in incorporated self-employment who arrived during 2011-2021 fared less badly, relative to earlier cohorts, in terms of business earnings than their counterparts in unincorporated businesses, while results concerning exits from self-employment are mixed in this respect.
Keywords: J15; J24; J71; 330; Self-employment; Immigrants; COVID-19; Refugee crisis